DOES INFORMAL LEARNING BRIDGE A RELATIONSHIP BETWEEN PUBLIC HEALTH EMPLOYEE MOTIVATION AND JOB SATISFACTION TOWARD PERFORMANCE? - Suryosukmono, Gerry; Praningrum, Praningrum; Pareke, Fahrudin Js (Universitas Brawijaya, Indonesia, 2022)
This study examines and analyzes the significant positive effect of job satisfaction and motivation on employee performance mediated by informal learning. The population of this study was employees of the Ministry of Health who worked in the Bengkulu Province based on the Ministry of Health Polytechnic and the Class III Port Office of Bengkulu Province. The number of respondents amounted to 100 people. The study was analyzed using the Structural Equation Modeling (SEM) method with PLS 3 analysis tool. Based on the research conducted, we found that job satisfaction had a significant positive effect on informal learning and employee performance directly. On the other hand, motivation positively affects performance, although it cannot affect performance. In addition, informal learning can also positively impact improving performance directly. However, informal learning cannot mediate job satisfaction and motivation in improving employee performance in the mediating relationship. This study provides implications for informal learning through informal discussions in the form of constructive feedback between leaders as mentors and employees, which are expected to motivate to improve employee performance on an ongoing basis.